1996 IEEE MTT-S International Microwave Symposium Digest
DOI: 10.1109/mwsym.1996.508504
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter-wave performance of chip interconnections using wire bonding and flip chip

Abstract: The performances of two different interconnection techniques for coplanar MMICs, wire bonding and flip chip, are investigated at millimeter-wave frequencies. By developing an accurate model for the interconnections, which is validated with experimental data up to 120 GHz, the limitations with respect to frequency and interconnection distance of either technique are pointed out, yielding useful data for the design of hybrid MMW-subsystems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(45 citation statements)
references
References 6 publications
1
43
0
1
Order By: Relevance
“…The difference D|S 21 | between on chip and flip chip measurements is the insertion loss of the bumps. This insertion loss matches the statements in [2] exactly. Photographs of the flip chip mounted MS-MMIC are shown in Fig.…”
Section: Simulation Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The difference D|S 21 | between on chip and flip chip measurements is the insertion loss of the bumps. This insertion loss matches the statements in [2] exactly. Photographs of the flip chip mounted MS-MMIC are shown in Fig.…”
Section: Simulation Resultssupporting
confidence: 78%
“…The common opinion is that MMICs designed in coplanar transmission line technology (coplanar waveguide, CPW) have a high compatibility with flip-chip mounting technology, while microstrip (MS) MMICs are not compatible. Various studies in the past have demonstrated design rules for finding the optimum bump height, distance or shape [2,3] in order to minimize the transition loss. In this paper, the proximity effect corresponding to the distance between chip and substrate is examined for both microstrip and coplanar MMICs.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative technology based on silicon germanium (SiGe) promises to provide truly low-cost millimeter-wave front-end MMICs while simultaneously maintaining the favorable performance of GaAs. Coplanar wirebond interconnects between chips could be low loss at 60 GHz, whereas multichip module technologies could well accommodate millimeter wave components along with intermediate frequency (IF) and baseband circuits [7]. The challenge will be to achieve high-volume production of high-performance compact 60 GHz transmitter/receiver modules (e.g., like those reported in [8]).…”
Section: Ghz Front-end Technologymentioning
confidence: 99%
“…Experimental [5], [6] and numerical [3], [7], [8] characterization typically neglect the variation in wire bond parameters such as the loop height or assume a particular configuration. In this paper, a comprehensive characterization of wire bond interconnects on air connecting two microstrip lines as a function of lengths, loop heights (tight and loose loops) and bond types (ball-crescent and wedge) is presented.…”
Section: Introductionmentioning
confidence: 99%